Evaluating ventilation system retrofits for high-rise residential buildings using a CONTAM model. (November 2021) - Fine, Jamie P.; Touchie, Marianne F.
Abstract: In Canada and the United States, pressurized corridor ventilation systems are common in older high-rise multi-unit residential buildings (MURBs). There is growing evidence that these systems exhibit poor performance, necessitating the evaluation of alternatives. This study used a CONTAM air flow model to compare six ventilation systems to the pressurized corridor, including various decentralized and direct-to-suite ducted configurations. The model was generated using field data from a representative 24-storey post-World War II MURB in Toronto, Canada, along with field data from the literature. Simulations were run for each system under cold (−16.1 °C, 3 °F) and warm (29.0 °C, 84.2 °F) outdoor conditions and the results were analyzed for the 2nd and 23rd levels. The novel contributions from this work are insights into air flow within the target building typology and the design recommendations that these insights permit. Key findings include: 1) Reliance on door undercuts to facilitate air flow from corridors to suites results in increased in/exfiltration across the exterior wall by up to 230% under cold conditions; 2) Automated air flow control at ducted supply terminals does not significantly improve the performance of any tested system; and 3) Inter-suite air flow is significant in all of the tested systems, with 20%–31% of the air in the 23rd level suite being attributed to either direct (5%–13%) or indirect (15%–18%) inter-suite air flow during the cold condition. We recommend reducing indirect inter-suite flow, where possible, and avoiding door undercuts and automated ducted supply terminal flow control. Highlights: An air flow model was generated in CONTAM of a 24-storey post-war high-rise MURB. Field and literature data were used to generate and validate the model. Pressurized corridors and six alternative ventilation strategies were analyzed. Ventilation, total, and inter-suite air flow rates were compared. Design recommendations were generated based upon model results.